Management of BRCA Tumour Testing in an Integrated Molecular Tumour Board Multidisciplinary Model - Azzollini, Jacopo; Vingiani, Andrea; Agnelli, Luca; Tamborini, Elena; Perrone, Federica; Conca, Elena; Capone, Iolanda; Busico, Adele; Peissel, Bernard; Rosina, Erica; Ducceschi, Monika; Mantiero, Mara; et al. (Frontiers in Oncology, 2022)
Tumour testing of the BRCA1/2 genes is routinely performed in patients with different cancer histological subtypes. To accurately identify patients with tumour-detected germline pathogenic variants (PVs) is a relevant issue currently under investigation. This study aims at evaluating the performance of the tumour-to-germline diagnostic flowchart model defined at our Institutional Molecular Tumour Board (MTB). Results from tumour BRCA sequencing of 641 consecutive unselected cancer patients were discussed during weekly MTB meetings with the early involvement of clinical geneticists for appropriate referral to genetic counselling. The overall tumour detection rate of BRCA1/2 PVs was 8.7% (56/641), ranging from 24.4% (31/127) in high-grade ovarian cancer to 3.9% (12/304) in tumours not associated with germline BRCA1/2 PVs. Thirty-seven patients with PVs (66%) were evaluated by a clinical geneticist, and in 24 of them (64.9%), germline testing confirmed the presence of the PV in blood. Nine of these patients (37.5%) were not eligible for germline testing according to the criteria in use at our institution. Cascade testing was subsequently performed on 18 relatives. The tumour-to-germline diagnostic pipeline, developed in the framework of our institutional MTB, compared with guideline-based germline testing following genetic counselling, proved to be effective in identifying a higher number of germline BRCA PVs carriers.